1998
DOI: 10.1021/ie970701d
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Equilibria of Chlorinated Organic Solvents onto Activated Carbon

Abstract: Adsorption equilibria of dichloromethane, 1,1,1-trichloroethane, and trichloroethylene on activated carbon were obtained by a static volumetric technique. Isotherms were measured for the pure vapors in the temperature range from 283 to 363 K and pressures up to 60 kPa for dichloromethane, 16 kPa for 1,1,1-trichloroethane, and 7 kPa for trichloroethylene, respectively. The Toth and Dubinin−Radushkevich equations were used to correlate experimental isotherms. Thermodynamic properties such as the isosteric heat o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 6 publications
2
23
0
Order By: Relevance
“…The HBT equation is used, since Reich et al recommend it, although the Rackett equation has been more popular with potential the-Ž . ory models Mehta and Danner, 1985;Yun et al, 1998 . Saturated vapor pressures are calculated by the Antoine equa-Ž .…”
Section: Potential Theory Approach For Isotherm Modelsmentioning
confidence: 99%
“…The HBT equation is used, since Reich et al recommend it, although the Rackett equation has been more popular with potential the-Ž . ory models Mehta and Danner, 1985;Yun et al, 1998 . Saturated vapor pressures are calculated by the Antoine equa-Ž .…”
Section: Potential Theory Approach For Isotherm Modelsmentioning
confidence: 99%
“…Despite its high energy density, long life and fast charging capacity, AC is categorized as an electric double-layer capacitor (EDLC), which means that energy can be stored at the electrolyte/electrolyte double-layer interface (Ali et al 2019a,b;Simon et al 2012;Yan 2014). Based on a review of the literature, it is safe to assume that the majority of AC research to date have focused on equilibrium conditions, with the primary goal of these studies being the establishment of an acceptable adsorption isotherm for pollutant removal (Cal et al 1994;Yun et al 1998). Limited researchers (Yun et al 1998;Tanthapanichakoon et al 2005) have observed iron corrosion prevention by AC phenomenally; however, there is a deficiency in basic research on the preservation properties of AC.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a review of the literature, it is safe to assume that the majority of AC research to date have focused on equilibrium conditions, with the primary goal of these studies being the establishment of an acceptable adsorption isotherm for pollutant removal (Cal et al 1994;Yun et al 1998). Limited researchers (Yun et al 1998;Tanthapanichakoon et al 2005) have observed iron corrosion prevention by AC phenomenally; however, there is a deficiency in basic research on the preservation properties of AC. The purpose of this study was to determine the applicability of AC in the prevention of iron corrosion under various situations and to investigate the mechanism behind the process.…”
Section: Introductionmentioning
confidence: 99%
“…Developing materials for the adsorption of volatile organic compounds (VOCs) from air is important for improving separations for industrial processing and environmental protection. A wide variety of porous solids have been studied for VOC capture, including activated carbon, polymeric resins, zeolites, organoclays, and hydrophobic aerogels. Development of new types of adsorbents typically addresses improvement of total adsorption capacity and rate of adsorption as primary objectives. In addition to these parameters, reversible adsorption and chemical selectivity are also important factors in developing sorbents for VOC capture.…”
Section: Introductionmentioning
confidence: 99%